Inward FDI spillovers and innovation capabilities in Chinese business: exploring the moderating role of local industrial externalities. Issue 8 (14th September 2017) - Li, Jian; Sutherland, Dylan; Ning, Lutao
ABSTRACT: It is generally believed foreign direct investment (FDI) has spillover effects which can affect the innovation capabilities of local firms in host countries. Comparatively little, however, is known about the contingent local contextual factors that influence how these FDI spillovers can be captured. Integrating the literature on FDI knowledge spillovers with that on inter- and intra-industrial externalities, we explore how local industrial agglomeration moderates the effect of FDI knowledge spillovers on innovation in the emerging market context of China. Empirical estimates, based on panel data of 1610 listed indigenous Chinese firms recorded between 2000 and 2010, indicate that such spillovers are more easily captured in industrially diverse settings. By contrast, industrial specialisation negatively moderates this relationship. Theoretical and practical implications are discussed.